University virtual learning environment (UVLe) and intellectual behaviors of teachers and students - Pitagan, Ferdinand B. (2005)
The study was conducted to determine the intellectual behaviors exhibited by teachers and students vis-a-vis UVLe, to assess the correlation between these intellectual behaviors, and to identify the factors that contribute to the level of these intellectual behaviors. It employed the descriptive research method. The study used data gathered from a survey conducted in classes of teacher/s in each of the selected colleges of 21 teachers and 429 students. It was revealed that there is a moderate to high level of intellectual behaviors regarding UVLe, high correlations between all these intellectual behaviors and varied relationship between factors and intellectual behaviors. The findings are necessary to improve the level of awareness, services and support of UVLe.